Bias factors associated with assessing the validity of university teaching: a hierarchical linear model Factores de sesgo asociados a la validez de la evaluación docente universitaria: un modelo jerárquico lineal. - Raciel Acevedo Alvarez; Nuria Mairena Rodríguez (Arizona State University, 2006)
The present study analyzes the variables that are intrinsically linked with the student, professor and class environment in relation to the university educational evaluation questionnaires. The participants in the study were 374 students with an age mean of 19.9 and 29 professors with an age mean of 36 from 3 different departments at the Universidad de Costa Rica (UCR) at the city of Guanacaste. The hierarchical lineal models were used for the data analysis, a quantitative methodology which facilitates the evaluation of the determinants which affect the results of the study. However, only four of these determinants were associated with the evaluation concerned, class size, enrolment year, department type and forecasted achievement levels. The results obtained from the study demonstrate that these kinds of evaluation are valid despite the results being slightly affected by a range of factors from externalities to teacher competence. El presente estudio analiza las variables del estudiante, la clase y el profesor asociadas con el sesgo en los cuestionarios aplicados a los estudiantes en la evaluación docente universitaria. En la propuesta han participado 374 estudiantes y 29 profesores de tres departamentos de la Universidad de Costa Rica (UCR), sede de Guanacaste, con una media de edad de 19.9 para los estudiantes y de 36 años los profesores. Para el análisis de los datos se utilizaron los modelos jerárquicos lineales, una metodología cuantitativa, cuyas estimaciones permitieron comprobar que de todos los determinantes incluidos en el estudio, solamente, cuatro de ellos (número de estudiantes en el curso, cantidad de años en la institución, tipo de departamento al que pertenece el estudiante y expectativa de nota) estaban ligeramente asociados a este tipo de evaluación. Los resultados demuestran que estas evaluaciones son válidas y se ven poco afectadas por los elementos externos a la competencia docente.